Mechanochemical Hydrolysis of Polysaccharide Biomass: Scope and Mechanistic Insights - Kobayashi, Hirokazu; Fukuoka, Atsushi (ChemPlusChem (Weinheim, Germany), 2024)
Mechanical forces can affect chemical reactions in a way that thermal reactions cannot do, which may have a variety of applications. In biomass conversion, the selective conversion of cellulose and chitin is a grand challenge because they are the top two most abundant resources and recalcitrant materials that are insoluble in common solvents. However, recent works have clarified that mechanical forces enable the depolymerization of these polysaccharides, leading to the selective production of corresponding monomers and oligomers. This article reviews the mechanochemical hydrolysis of cellulose and chitin, particularly focusing on the scope and mechanisms to show a landscape of this research field and future subjects. We introduce the background of mechanochemistry and biomass conversion, followed by recent progress on the mechanochemical hydrolysis of the polysaccharides. Afterwards, a considerable space is devoted to the mechanistic consideration on the mechanochemical reactions. Mechanical forces can affect chemical reactions in a way that thermal reactions cannot do. They enable the depolymerization of the polysaccharides, leading to the selective production of corresponding monomers and oligomers. This review article summarizes the latest understanding of mechanochemical conversion of the polysaccharides and the reaction mechanisms to show a landscape of this research field and remaining issues.